2020
DOI: 10.1186/s12944-020-01404-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the serum levels of Meteorin-like in patients with inflammatory bowel disease and its association with inflammatory cytokines

Abstract: Background Meteorin-like (Metrnl) is an adipokine with insulin sensitizing and anti-inflammatory properties that has been discovered recently. The relation among Metrnl, Inflammatory Bowel Disease (IBD), and obesity has been unexplored yet. Methods The present study was conducted on 54 healthy control, 42 Ulcerative Colitis (UC), and 43 Crohn’s disease (CD) patients who were diagnosed by pathological examination. In all participants, serum levels of adiponectin, Metrnl, interleukin (IL)-6, and Tumor necrosis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Several studies demonstrated that serum IL‐41 levels were decreased in T2D patients compared with the healthy controls 21–23 . Moreover, serum IL‐41 concentrations were considerably lower in patients with coronary artery disease 15 and ulcerative colitis and Crohn's disease 24 in comparison with healthy controls. In this study, we also observed a decrease in serum IL‐41 levels in GD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that serum IL‐41 levels were decreased in T2D patients compared with the healthy controls 21–23 . Moreover, serum IL‐41 concentrations were considerably lower in patients with coronary artery disease 15 and ulcerative colitis and Crohn's disease 24 in comparison with healthy controls. In this study, we also observed a decrease in serum IL‐41 levels in GD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results showed nitric oxide synthase iNOS and common inflammatory factors (IL-1β, IL-6, TNF-α) play a key role in inflammation development (29,30). Following LPSstimulated macrophages, the expression of iNOS, IL-1β, IL-6, and TNF-α related genes increased significantly.…”
Section: Effect Of Different Rchp-s Concentrations On Cytokine Secretionmentioning
confidence: 98%
“…There are reports that serum levels of retinol-binding protein 4, another adipokine linked to the metabolic syndrome [ 73 , 119 ], has been reported to be elevated in IBD patients [ 76 ] and inversely correlated with disease activity [ 120 ]. Finally, meteorin-like, a novel adipokine with insulin sensitizing and anti-inflammatory properties, has been recently detected as decreased in patients with IBD [ 121 ]. Meteorin-like levels were inversely related with BMI, TNF-α, and IL-6, which suggested a possible relation with the inflammatory process in IBD.…”
Section: Adipokinesmentioning
confidence: 99%